How to babysit a leopard and other true stories from our travels across six continents - Lewin, Ted 1935-; Lewin, Betsy 1937- (A Neal Porter book, 2015)
"From Africa to Asia Pacific, from Europe to the United States of America, acclaimed authors/illustrators Ted and Betsy Lewin have roamed the earth taking on snakes, tracking mountain gorillas, and generally trying to avoid being eaten by various jungle creatures. Packed with pencil drawings, full-color illustrations, and captivating photographs, there is not a single dull moment as Ted and Betsy take the reader through their dramatic, funny, and often poignant stories...all true! A Neal Porter Book"...